Computing tumor trees from single cells. Issue 1 (December 2016) - Davis, Alexander; Navin, Nicholas
Abstract Computational methods have been developed to reconstruct evolutionary lineages from tumors using single-cell genomic data. The resulting tumor trees have important applications in cancer research and clinical oncology. Please see related Research articles:http://genomebiology.biomedcentral.com/articles/10.1186/s13059-016-0929-9 andhttp://genomebiology.biomedcentral.com/articles/10.1186/s13059-016-0936-x .